2011
DOI: 10.1016/j.ajpath.2011.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of the Endoplasmic Reticulum Stress Sensor BiP/GRP78 Predicts Response to Chemotherapy and Determines the Efficacy of Proteasome Inhibitors in Diffuse Large B-Cell Lymphoma

Abstract: Activation of the endoplasmic reticulum (ER) stress pathway is associated with poor response to doxorubicin-containing regimens, such as rituximab, cyclophosphamide, hydroxydaunorubicin (doxorubicin), vincristine and prednisone (R-CHOP), in patients with diffuse large B-cell lymphoma (DLBCL). Bortezomib, a proteasome inhibitor, interferes with ER responses and improves survival in patients with aggressive hematologic malignant tumors, although its use in DLBCL patients remains controversial. The 78-kDa glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 52 publications
0
49
0
2
Order By: Relevance
“…Цей фактор росту судин в умовах гіпоксії діє також як фактор виживан-ня епітеліальних клітин кришталика шляхом збереження сталої експресії протеїну BCL-2, який попереджає транслокацію протеїну BAX із цитозоля до зовнішньої мембрани мітохондрій [60]. Підвищена експресія шапе-рону HSPA5 у багатьох злоякісних новоутво-реннях, який значною мірою визначає також чутливість пухлинних клітин до хіміотерапії, робить його перспективною мішенню для по-шуку нових шляхів протипухлинної терапії [17,61].…”
Section: рис 3 схематичне зображення структури Ern1 в ендоплазматичunclassified
“…Цей фактор росту судин в умовах гіпоксії діє також як фактор виживан-ня епітеліальних клітин кришталика шляхом збереження сталої експресії протеїну BCL-2, який попереджає транслокацію протеїну BAX із цитозоля до зовнішньої мембрани мітохондрій [60]. Підвищена експресія шапе-рону HSPA5 у багатьох злоякісних новоутво-реннях, який значною мірою визначає також чутливість пухлинних клітин до хіміотерапії, робить його перспективною мішенню для по-шуку нових шляхів протипухлинної терапії [17,61].…”
Section: рис 3 схематичне зображення структури Ern1 в ендоплазматичunclassified
“…Although GRP78 expression is maintained at low basal levels in major adult organs, it has often been found to be upregulated in cancer cells (2,16,26,34,36). Studies have shown that although the majority of GRP78 resides in the ER lumen, a fraction of it exists as an ER transmembrane protein, with its NH 2 portion in the cytosol.…”
mentioning
confidence: 99%
“…[53][54][55] In our patients, the simultaneous expression of a latency III pattern associated with intratumoral EBV replication seems to detect a subset of heavily immunosuppressed group of patients with lower rates of rejections or graft vs host disease and higher rates of cytomegalovirus reactivations. These patients have significantly lower overall survival rates and shorter time to develop lymphomas.…”
Section: Epstein-barr Virus Replication and Post-transplant Lymphopromentioning
confidence: 99%